HGG-30. PEDIATRIC GLIOSARCOMA WITH AND WITHOUT NEUROFIBROMATOSIS TYPE 1: A WHOLE-EXOME COMPARISON OF TWO PATIENTS. Issue 2 (22nd June 2018) - Graham, Richard T; Bell, Erica Hlavin; Webb, Amy; Timmers, Cynthia; Robison, Nathan; Palmer, Joshua; Finlay, Jonathan L; Chakravarti, Arnab
Abstract: BACKGROUND/OBJECTIVE: Gliosarcoma is a WHO grade IV histologic variant of glioblastoma that occurs very rarely among pediatric patients, even more so amongst Neurofibromatosis Type 1 (NF1) individuals. Patients with NF1-associated high-grade gliomas (HGGs) reportedly have better clinical outcomes than others despite their germline tumor-suppressor mutation. Since molecular data to explain this are lacking, we compared tumor exomes from two pediatric gliosarcoma patients, one with NF1 (P1) and one without (P2). PATIENTS/METHODS: Two patients with gliosarcoma (ages 12 and 11 years), were treated with resection (gross total for P1 and near-total for P2), bevacizumab, temozolomide and irradiation. We performed whole-exome sequencing (WES, Agilent SureSelect V6 + Cosmic) on tumor and blood to determine both germline and somatic mutations. Tumor mutations were filtered based on predicted deleterious effects and a list of genes was compared to online pediatric tumor databases (PeCan and PedcBioPortal). RESULTS: P1 is alive without progression after 5.8 years. P2 developed tumor recurrence after 2 years, expiring 4.6 years from diagnosis. Tumor DNA revealed a lower mutational burden in P1 (NF1) than in P2 including some genes which have been previously reported in pediatric HGGs (e.g. IKBKB in P2). However, there was no overlap in specific gene mutations. CONCLUSIONS: This is the first report of WES in pediatric gliosarcoma. The differences in mutational burden between these patients might explain improved survival outcomes for HGG patients with NF1 as well as shedding light on the different mutational processes leading to their tumors. Further molecular analyses including methylation profiling are ongoing.